VIEWS OF PRESERVICE CLASROOM TEACHERS ABOUT THE INVOLVEMENT OF NONGOVERNMENTAL ORGANIZATIONS IN EDUCATION - Tuğba SELANİK AY (International Journal of Eurasia Social Sciences, 2016)
Nongovernmental organizations can be defined as those organizations which employ information consciously and have higher levels of confidence. Such organizations could be easily organized and are dependent on an understanding of state based on legal considerations. These organizations are the reflection of the relationship between state and civil society. In education one of the major goals should be to raise the usability of theoretical information in daily life. In this context it can be argued that nongovernmental organizations should involve in education activities. This study aims at identifying the views of preservice teachers about the use of NGOs in education. The participants of the study were 136 preservice classroom teachers during the school year of 2015-2016. The data of the study were collected through a questionnaire with eight open-ended items. The data obtained were examined using descriptive analysis and are complemented by direct quotations from the views of the participants. The findings indicated that only 19,86% of the participants were the members of the NGOs and that some of them were planning to join NGOs (43,38%). There were also those who were not planning to join NGOs (36,76%). Regarding the NGOs which some participants were members were found to be Educational Volunteers Foundation of Turkey, Health and Education Foundation for Children with Leukemia and Turkey Combating Soil Erosion, for Reforestation and the Protection of Natural Resources Foundation. The participants reported that their preference over NGOs were affected by media outlets, social media, and their friends’ views. They also argued that NGOs have invaluable contributions to them and to primary school students and collaborations with NGOs may be useful in the courses such as social studies, life sciences and science.